Os espaços lúdicos como elementos formadores em uma creche do município de Santo André - Araujo, Djanira Alves Biserra (2016)
The object of this research are the recreational areas of the nursery. We aim to observe and analyze how teachers take ownership of these spaces in order to make them forming elements. As a specific purpose we list the following: check what teachers mean by recreational areas of the nursery observing how babies play. We seek to answer the following question: What teachers understand by recreational areas of the nursery? As babies play in the perception of the teachers? The universe is a nursery located in the municipality of Santo André which serves 210 (two hundred and ten) infants up to three years old and subjects participants are four teachers. The methodology is qualitative nature of the kind intervention research guided in action research. The data collection instruments are the observation made by the researcher in different recreational areas of the nursery and conversation circles with teachers in times of Meetings Weekly Pedagogic (RPS) and planning, followed by registration, as well as interviews. The theoretical framework used Kishimoto (2012); Oliveira (2012) and Vygotsky (1998), to support the category playfulness; Oliveira (2012); Kramer and Milk (1996), to support the category Childhood Education; Barbosa and Horn (2001), Forneiro (1998), Souza (2001), to support for the category space; Nóvoa (1992); Kramer (1994) and Freire (2004), Vasconcelos (2004), to support the category continued teacher training. As results we observed that teachers have become more involved in educational work with babies, realize how your posture is crucial in the development process of small, contribute more to each other in moments of conversation circles if further offer to create most appropriate strategies to the age group of very small babies, recognize the potential of babies as contributors to the planning and builders of knowledge itself, and recognize the importance of the recreational areas of the nursery as forming elements. The RPS moments have also been more significant considering the participation of all.